PENGARUH KONTRAK PSIKOLOGIS RELASIONAL DAN KONTRAK PSIKOLOGIS TRANSAKSIONAL TERHADAP KOMITMEN ORGANISASIONAL (Studi pada Karyawan Non Medis di Rumah Sakit Roemani Muhammadiyah Kota Semarang) - Mutiara Hadi, Dina; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2018)
This research conducted based on research gap from previous reaseaches about relational dan transactional psychological contract and it’s impact to organizational commitment. However, previous researches only discussed psychological contract in general, and there was no detailed explanation about relational dan transactional psychological contract. This research intended to analyze the impact of Transactional dan Relational Psychological Contract to Organizational Commitment.This research conducted to non-medical employees of Roemani Muhammadiyah Hospital of Semarang, with 156 employees as the population. This research using snowball sampling as the sample collecting methode, with 81 employees as the sample gathered. This research also used SPSS multiple regression as the data analizing methode.The result of this research indicate that Relational Psychological Contract has a significan positive impact organizational commitment. In contrast, this research also found that transactional psychological contract has a negative significan negative impact to organizational commitment.